Philosophical Toys Today - Dvořák, Tomáš (Teorie vědy / Theory of Science, 2013)
PHILOSOPHICAL TOYS TODAY Abstract: The article introduces a thematic issue of the journal Theory of Science that attempts to revive the category of "philosophical toys" - objects and instruments designed for experimental scientific research that simultaneously played crucial role in the creation of the modern visual culture. It claims that to fully understand their nature and the kind of experience philosophical toys induce, it is necessary to situate their origins in eighteenth-century experimental science and aesthetics and proposes to approach them as perceptual and cognitive extensions. Keywords: philosophical toys; scientific instruments; modern visual culture Filosofické hračky dnes Abstrakt: Studie uvádí tematické číslo časopisu Teorie vědy věnované aktualizaci koncepce „filosofických hraček" - předmětů a přístrojů určených k experimentálnímu vě- deckému zkoumání, jež zároveň výrazně ovlivnily utváření moderní vizuální kultury. Abychom plně porozuměli povaze těchto přístrojů a typu zkušenosti, již sebou přiná- šejí, je třeba jejich původ situovat do experimentální vědy a estetiky osmnáctého století a chápat je jako percepční a kognitivní extenze. Klíčová slova: filosofické hračky; vědecké přístroje; moderní vizuální kultura